2017 IEEE International Conference on Smart Computing (SMARTCOMP) 2017
DOI: 10.1109/smartcomp.2017.7946999
|View full text |Cite
|
Sign up to set email alerts
|

Delay-Aware Design, Analysis and Verification of Intelligent Intersection Management

Abstract: Abstract-With the rapid advancement of autonomous driving and vehicular communication technology, intelligent intersection management has shown great promise in improving transportation efficiency. In a typical intelligent intersection, an intersection manager communicates with autonomous vehicles wirelessly and schedules their crossing of the intersection. Previous system designs, however, do not address the possible communication delays due to network congestion or security attacks, and could lead to unsafe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Importantly, it still not clear if and under which circumstances intelligent intersections can provide significant benefits. For example, [73] find that introducing only 10% human drivers into scenarios with AUVs can render intelligent intersections as useful as traffic lights, and [81] show that communication delays can severely impact performance. Therefore, the key question is whether a tradeoff in privacy is worthwhile.…”
Section: G Intelligent Intersectionsmentioning
confidence: 99%
“…Importantly, it still not clear if and under which circumstances intelligent intersections can provide significant benefits. For example, [73] find that introducing only 10% human drivers into scenarios with AUVs can render intelligent intersections as useful as traffic lights, and [81] show that communication delays can severely impact performance. Therefore, the key question is whether a tradeoff in privacy is worthwhile.…”
Section: G Intelligent Intersectionsmentioning
confidence: 99%
“…Furthermore, to elevate cooperation and efficiency in particular zones, they presented market mechanisms. In a different approach, Zheng et al [221] proposed a delay-tolerant IM protocol in terms of communication. Besides, a framework was devised for safety, performance and liveliness analysis of the protocol and showed that the system was collision free and decreased delay compared to the traffic lights.…”
Section: Safety and Efficiencymentioning
confidence: 99%
“…We then apply the cross-layer methodology to the design and verification of centralized autonomous intersections in [6]. In this application, vehicles approaching an intersection exchange information with an intersection manager via V2I messages, and the intersection manager decides the order for vehicles to pass the intersection.…”
Section: Cross-layer Design For Connected Vehiclesmentioning
confidence: 99%